A new species and new synonym in Rubus subgenus Cylactis (Rosaceae) - Wang, Qiu-Ping; Yang, Feng; Wang, Huan-Chong (Phytotaxa, 2019)
Rubus zixishanensis Huan C. Wang & Q. P. Wang, is described and illustrated as a new species endemic to Yunnan, Southwest China. It belongs to the subgenus Cylactis and is the only species with crimson petals in this subgenus. Rubus zixishanensis is most similar to R. arcticus, but clearly differs from the latter by its whole plant with tiny glandular hair, and stems creeping or decumbent, stipules narrowly lanceolate to linear, base shortly adnate to petioles, calyx abaxially setose, sepals consistently 5, petals crimson and pistils 5–9. In addition, the name R. naruhashii Yi Sun & Boufford, a replacement name of R. clivicola Walker, is treated as a taxonomic synonym of R. potentilloides W. E. Evans.